2023
DOI: 10.3390/molecules28083434
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and Fatty Acid Esters from Cyperus sexangularis Leaf and Their Antioxidant, Anti-Inflammatory and Anti-Elastase Properties

Abstract: Cyperus sexangularis (CS) is a plant in the sedges family (Cyperaceae) that grows abundantly in swampy areas. The leaf sheath of plants in the Cyperus genus are mostly used domestically for mat making, while they are implicated for skin treatment in traditional medicine. The plant was investigated for its phytochemical contents as well as its antioxidant, anti-inflammatory and anti-elastase properties. The n-hexane and dichloromethane leaf extracts were chromatographed on a silica gel column to afford compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Mbachu et al ( 2019 ) also identified 5-eicosene among the bioactive compounds in the essential oil of B. pinnatum . Fatty acid methyl esters (FAME) and fatty acids (FA) are known to possess low antioxidant activity (Pinto et al, 2017 ; Miya et al, 2023 ). However, a synergy in their antioxidant activity may explain the higher antioxidant activity of the PE compared to AA, as seen in Figure 2 , and the observed antioxidant activity of FA and FAME is evident in both the PE and NPE.…”
Section: Resultsmentioning
confidence: 99%
“…Mbachu et al ( 2019 ) also identified 5-eicosene among the bioactive compounds in the essential oil of B. pinnatum . Fatty acid methyl esters (FAME) and fatty acids (FA) are known to possess low antioxidant activity (Pinto et al, 2017 ; Miya et al, 2023 ). However, a synergy in their antioxidant activity may explain the higher antioxidant activity of the PE compared to AA, as seen in Figure 2 , and the observed antioxidant activity of FA and FAME is evident in both the PE and NPE.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that while these identified compounds may contribute significantly to the anti-inflammatory and antioxidant effects observed, there could be other bioactive molecules present in the extract that were not detected via LC-MS analysis. These undetected molecules such as fatty acids, carotenoids, and steroids may also play a significant role in the observed anti-inflammatory capacity of the extract [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further compounds identified included fatty acyls, such as decane, 6-ethyl-2-methyl-and octadecane, 3-ethyl-5-(2-ethylbutyl)-, which may contribute as surfactants in skincare products [24,25]. Fatty acid derivatives, such as 2-monolinolenin, 2TMS derivatives, and benzyl (6Z,9Z,12Z)-6,9,12-octadecatrienoate hold potential for their ability to provide antioxidant and anti-inflammatory effects on the skin, contributing to overall skin health and anti-aging properties [26][27][28]. Hydrocarbon derivatives, including cyclopentanol, 2-methyl-, trans-, and cyclooctane acetic acid, 2-oxo-, may have unique properties that can contribute to the sensory aspects and formulation of cosmetic products [29,30].…”
Section: Characterization Of Ethanolic Extracts Of P Boergesenii Usin...mentioning
confidence: 99%